2013
DOI: 10.1007/s13191-013-0335-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermocycling on Flexural Strength and Weibull Statistics of Machinable Glass–Ceramic and Composite Resin

Abstract: To evaluate the durability of machinable dental restorative materials, this study performed an experiment to evaluate the flexural strength and Weibull statistics of a machinable lithium disilicate glass-ceramic and a machinable composite resin after being thermocycled for certain cycles. A total of 40 bar-shape specimens of were prepared with the dimension of 20 mm × 4 mm × 2 mm, which were divided into four groups of 10 specimens. Ten specimens of machinable lithium disilicate glass-ceramic (IPS e.max CAD, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 26 publications
5
15
0
1
Order By: Relevance
“…In the present study, thermocycling did not cause significant decrease in the flexural-strength values of the LDS and PICN specimens. This finding was in agreement with previous studies that reported that LDS [ 25 ] and PICN are not influenced by thermocycling [ 26 , 27 ]. Thermal cycling or storing resin-based materials in water were reported to cause polymer softening due to water penetrating the resin matrix [ 28 ].…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, thermocycling did not cause significant decrease in the flexural-strength values of the LDS and PICN specimens. This finding was in agreement with previous studies that reported that LDS [ 25 ] and PICN are not influenced by thermocycling [ 26 , 27 ]. Thermal cycling or storing resin-based materials in water were reported to cause polymer softening due to water penetrating the resin matrix [ 28 ].…”
Section: Discussionsupporting
confidence: 94%
“…However, these results were in agreement with another investigation in which prolonged water storage influenced flexure strength of some tested materials and did not influence the flexure modulus of all tested composite materials and another investigation was confirming the present results in which thermo-cycling did not influence flexure properties of nano-filled composite [17,30].…”
Section: Discussionsupporting
confidence: 93%
“…However, in literatures, there are variable techniques of sample storage before mechanical testing. Composite test samples may be stored at room temperature, body temperature, or thermo-cycled to represent temperature variation in the oral cavity [7][8][9][10][11][12][13][14][15]17]. In addition, water was used as an aging solution in several studies to mimic the wet environment in the oral cavity [4,[18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, many authors (18)(19)(20)(21)(22) noticed a decrease in the surface micro-hardness of composite resins after immersion of food simulating liquids. This is related to the susceptibility of polymeric matrix to sorption of different liquids.…”
Section: Discussionmentioning
confidence: 99%